A Ready-to-Use Single- and Duplex-TaqMan-qPCR Assay to Detect and Quantify the Biocontrol Agents Trichoderma asperellum and Trichoderma gamsii - Gerin, Donato; Pollastro, Stefania; Raguseo, Celeste; De Miccolis Angelini, Rita M.; Faretra, Francesco (Frontiers in Microbiology, 2018)
Trichoderma asperellum strain ICC 012 and Trichoderma gamsii strain ICC 080 (TG), the microbial active ingredients of RemedierTM (ISAGRO, Novara, Italy), are biocontrol agents (BCAs) employable for crop protection against a wide range of fungal pathogens, including soil-borne pathogens and fungi involved in grapevine trunk disease. In this study, single and duplex real-time quantitative PCR (qPCR) methods to detect and quantify T. asperellum and T. gamsii were developed. Primers/probe sets were designed on the T. asperellum and T. gamsii rpb2 genes and tested for specificity on a panel of microorganisms commonly associated with grape wood and soil. No differences were observed comparing single- and duplex-qPCR assays on different BCAs, 1 pg of target DNA was detected approximately at Cq=34. R2 values and the efficiency were always equal to 0.99 and >80%, respectively. The detection limit of the duplex-qPCR assay on artificially inoculated samples was 2x103 and 4x104 conidia g-1 of grape wood tissue and soil, respectively. The methods will be useful to better schedule BCA application in the field and in grapevine nurseries, as well as for investigating the dynamic of BCA populations.